Social reporting disclosure based on Maqasid Al-Shariah / Wan Adibah Wan Ismail and Khairul Anuar Kamarudin - Wan Ismail, Wan Adibah; Kamarudin, Khairul Anuar (Faculty of Accountancy, UiTM Kedah, 2019)
Corporate Social Responsibility disclosure (CSRD) refers to systematic voluntary disclosure of information related to social activities performed by corporations for the betterment of society and a healthier environment. In return, the companies expect that the voluntary commitment will benefit them to gain higher profit. There is also competitive advantage that companies believe they can enjoy by being socially responsible. The corporations expect that effective communication about social, environmental and economic contribution; will give opportunity to strengthen the relationship either with suppliers, customers or employees. However, companies only willingly do so if the potential benefits exceed the estimated costs. Consequently, companies that claim it is too costly do not provide adequate information and give misleading information. Organisations also consider only the salience on shareholders and creditors whilst they ignore the other stakeholders such as the community, employees and government in providing information. As such, the reporting should be more holistic and transparent.